Clinical and biochemical characterization of hepatitis B surface antigen-positive patients with or without Helicobacter pylori co-infection at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Belayneh, Mekuriaw; Tegegne, Bantayehu Addis; Lemma, Mulualem; Abay, Zenahebezu; Belyhun, Yeshambel (Frontiers in Immunology, 2025)
BackgroundHepatitis B virus (HBV) is a major global public health issue and the most common etiology of chronic liver disease (CLD). The relationship between Helicobacter pylori and HBsAg+ patients was not well investigated and has attracted much scientific and clinical interest, although the relationship remains controversial.ObjectiveThis study aimed to assess the clinical and biochemical characteristics of HBsAg+ liver disease patients with and without H. pylori infection.MethodsFrom April 1, 2021, to March 30, 2022, a hospital-based cross-sectional study was done at the University of Gondar Comprehensive Specialized Hospital on 384 known HBsAg+ liver disease patients recruited using a convenient sampling technique. All the HBsAg+ patients were tested for fecal H. pylori antigen, and blood specimens were analyzed for ALT, AST, ALP, ALB, TP, BILT, TG, and TChol tests using an automated biochemistry analyzer. GraphPad Prism 8.02 and SPSS 25 were used for data analysis, considering a statistically significant P-value of 0.05.ResultsH. pylori co-infection was found in 153 (39.8%) of HBsAg+ study participants. ALT, AST, and total cholesterol mean levels were significantly higher in patients co-infected with H. pylori (p<0.04). Portal hypertension (47.8%), variceal bleeding (60.7%), and hepatocellular carcinoma (HCC) (57.5%) were more common (p< 0.01) in patients with HBV and H. pylori co-infection.ConclusionsALT, AST, and TChol mean levels were higher in H. pylori co-infected HBsAg+ patients. Our findings showed that H. pylori has a role in the elevation of clinical and biochemical parameters in HBsAg+ liver diseases.